2019
DOI: 10.1111/btp.12664
|View full text |Cite|
|
Sign up to set email alerts
|

Shear adhesive performance of leaf‐cutting ant workers (Atta cephalotes)

Abstract: Wingless arboreal ants must resist the force of gravity while traversing substrates in their environment. For leaf‐cutting ants like Atta cephalotes, foraging may also include a ca. 30 m vertical descent while carrying a load 1–6 times their body mass. We hypothesized that heavier and larger ants would carry heavier and larger loads and that adhesive performance would positively correlate with load mass. We found no relationship between ant mass, body length, head width, or adhesive performance, and the load s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…majors, leaf carrying workers and "riders", who were smaller than leaf-carrying workers who climb leaves being carried by other workers to deter predation), not specifically on the size of individual workers. This resulted in proportionally less adhesion against sheering forces for the majors compared to regular workers and although riders had the greatest proportional tarsal pad size, carrying workers had the greatest adhesive strength, suggesting that other factors beyond tarsal pad size are at play when determining their grip strength, against shearing forces (Stark et al, 2019). However, in terms of raw adhesive strength, the majors produced the greatest adhesive strength.…”
Section: How Does Trail Gradient Affect the Size Of The Ants Who Choomentioning
confidence: 93%
See 4 more Smart Citations
“…majors, leaf carrying workers and "riders", who were smaller than leaf-carrying workers who climb leaves being carried by other workers to deter predation), not specifically on the size of individual workers. This resulted in proportionally less adhesion against sheering forces for the majors compared to regular workers and although riders had the greatest proportional tarsal pad size, carrying workers had the greatest adhesive strength, suggesting that other factors beyond tarsal pad size are at play when determining their grip strength, against shearing forces (Stark et al, 2019). However, in terms of raw adhesive strength, the majors produced the greatest adhesive strength.…”
Section: How Does Trail Gradient Affect the Size Of The Ants Who Choomentioning
confidence: 93%
“…Examinations of the tarsal pads found that the size of these tarsal pads did not scale proportionately with ant size (Stark et al, 2019). However, this study was focused on the roles that the ants played (i.e.…”
Section: How Does Trail Gradient Affect the Size Of The Ants Who Choomentioning
confidence: 94%
See 3 more Smart Citations